2011
DOI: 10.1063/1.3592192
|View full text |Cite
|
Sign up to set email alerts
|

Use of Raman spectroscopy to determine the site occupancy of dopants in BaTiO3

Abstract: Chemical doping is one of the major methods by which the properties of BaTiO3 are modified to induce various device characteristics. Doping strategies are generally separated into iso- and alio-valent (donors and acceptors) and into A- and B-site species within the perovskite structure. The A1g octahedral breathing mode at ∼800 cm−1 in BaTiO3 is Raman inactive for compositions with single B-site species. However, this mode becomes Raman active if more than one B-site species is present, including titanium vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(74 citation statements)
references
References 13 publications
8
64
1
1
Order By: Relevance
“…3, see Fig. 4) at about 830 cm -1 is clearly related to doping on the B site, as previously reported for Zr-doped BT (BaZrxTi1-xO3) [19]and (1-x)BaTiO3-xLaYbO3 solid solutions [5], since its intensity increases with the dopant level.…”
Section: Dielectric Propertiessupporting
confidence: 59%
“…3, see Fig. 4) at about 830 cm -1 is clearly related to doping on the B site, as previously reported for Zr-doped BT (BaZrxTi1-xO3) [19]and (1-x)BaTiO3-xLaYbO3 solid solutions [5], since its intensity increases with the dopant level.…”
Section: Dielectric Propertiessupporting
confidence: 59%
“…Pokorný et al have stated that the appearance of A 1g mode is a good indication of doping in the B-sites of a perovskite lattice. Additionally, this peak has been hardly observed in compositions with A-site doping [41]. Therefore, it may be concluded that, beside the formation of a liquid phase during sintering, the Bi additive is also partially incorporated into the structure of BCZT + Bix samples.…”
Section: Resultsmentioning
confidence: 83%
“…The vibrational modes are indexed in the diagram. Based on the Pokorny'work[27], the modes for x = 0 were assigned as a single crystal BaTiO 3 . In the regions from low to mid-wavenumber, the Raman spectrum of pure tetragonal BaTiO 3 was characterized by a sharp band at ~170 cm -1 , a "silent" mode at ~305 cm -1 , asymmetric broader bands at ~270 cm -1 , 515 cm -1 and the high-frequency LO modes at around 715 cm -1 [28].…”
mentioning
confidence: 99%